COMMUNICATION THEORIES IN PRACTICE: A STUDY OF SMALL HINDI NEWSPAPERS IN INDIA - Kumar, Mukesh (International Journal of Research -GRANTHAALAYAH, 2023)
This paper investigates how communication and press theories are enacted, reshaped and reinterpreted through the everyday practices of small Hindi newspapers in India. Based on an empirical study of 38 small Hindi newspapers across 19 Indian states, the research analyses the operationalisation of key press and communication theories including Libertarian Theory, Social Responsibility Theory, Democratic Participant Media Theory, Development Communication, Agenda-Setting and Communication for Social Change. The findings demonstrate that small Hindi newspapers play a significant role in shaping local public discourse by foregrounding issues related to governance, development, social justice, and everyday civic concerns that often remain marginal in mainstream media coverage. While watchdog journalism reflects the normative ideals of press freedom, the study reveals persistent structural constraints such as dependence on government advertising and regulatory mechanisms that complicate editorial autonomy. At the same time strong reader engagement, participatory formats and locally grounded reporting practices highlight the relevance of democratic participation and development-oriented communication theory. This paper challenges the adequacy of universal, market-driven assumptions embedded in dominant communication theories.